Field emission properties of ZnO nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Chakravarty, Disha; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
{Electron emission properties of electrodeposited ZnO nanosheet arrays grown on Indium tin oxide coated glass substrates have been studied. Influence of oxygen vacancies on electronic structures and field emission properties of ZnO nanosheets are investigated using density functional theory. The oxygen vacancies produce unshared d electrons which form an impurity energy state; this causes shifting of Fermi level towards the vacuum, and so the barrier energy for electron extraction reduces. The ZnO nanosheet arrays exhibit a low turn-on field of 2.4 V/mu m at 0.1 mu A/cm(2) and current density of 50.1 mu A/cm(2) at an applied field of 6.4 V/mu m with field enhancement factor

Emerging energy applications of two-dimensional layered materials - Late, Dattatray J.; Rout, Chandra Sekhar; Chakravarty, Disha; Ratha, Satyajit (Canadian Chemical Transactions, 2015)
Atomically thin semiconducting transition metal dichalcogenides (TMDCs) layered materials have recently been emerged as an exciting area of research due to accessibility for easy synthesis using various chemical and physical methods. These two-dimensional (2D) layered materials with single layer have direct and wide band gap due to which, they are more suitable for nanoelectronics and optoelectronics device applications. Here, we present a review of the energy related aspects of atomically thin layered materials like MoS2, WS2, MoSe2, WSe2, InSe, GaSe, GaTe, MoTe2, WTe2 etc. for supercapacitor, solar cell, lithium ion battery and water splitting application. By significantly assessing various materials and comparing their performances with challenging technology, the advantages and disadvantages of this promising area of energy materials are recognized, which may provide guidelines for future progress.

Exfoliation of bulk inorganic layered materials into nanosheets by the rapid quenching method and their electrochemical performance - Chakravarty, Disha; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report herein the results of our investigations on the synthesis of transition-metal dichalcogenide (TMDC) semiconductor layered materials of MoS2, WS2, MoSe2, and WSe2 by the rapid quenching method. The bulk powders were added to deionized water in a polypropylene tube and subsequently flushed with argon gas. Thirty rapid freezing (30 s in a liquid nitrogen bath) and heating (20 min in an oil bath at 60 degrees C) cycles were then carried out. The reaction product was obtained in a yield in excess of 60 wt.-%, which indicates that the method can be utilized on an industrial scale for the production of 2D nanosheets. The as-synthesized products were then characterized by TEM, which revealed nanosheet-like morphologies. Raman spectroscopy confirmed the high quality of the nanosheet samples. The exfoliated samples also showed good electrochemical performance. Of the TMDC samples investigated, the WSe2 nanosheets were found to give the best performance due to their uniform morphology, large surface area, and fewest number of defects.
Keywords: chalcogenides; Electrochemistry; Layered compounds; Molybdenum; Nanostructures; Tungsten

Graphene quantum dots as enhanced plant growth regulators: effects on coriander and garlic plants - Chakravarty, Disha; Erande, Manisha B.; Late, Dattatray J. (Journal of the Science of Food and Agriculture, 2015)
BACKGROUNDWe report investigations on the use of graphene quantum dots for growth enhancement in coriander (Coriandrum sativam L.) and garlic (Allium sativum) plants. The as-received seeds of coriander and garlic were treated with 0.2 mg mL(-1) of graphene quantum dots for 3 h before planting. RESULTSGraphene quantum dots enhanced the growth rate in coriander and garlic plants, including leaves, roots, shoots, flowers and fruits, when the seeds were treated with graphene quantum dots. CONCLUSIONOur investigations open up the opportunity to use graphene quantum dots as plant growth regulators that can be used in a variety of other food plants for high yield. (c) 2015 Society of Chemical Industry
Keywords: farming; food; graphene quantum dots; nanotechnology; plant growth regulator

Microwave and hydrothermal syntheses of WSe2 micro/nanorods and their application in supercapacitors - Chakravarty, Disha; Late, Dattatray J. (RSC Advances, 2015)
WSe2 micro/nanorods were synthesized using one step microwave and hydrothermal methods. The as synthesized micro/nanorod samples of WSe2 were characterized using various characterization techniques such as SEM, TEM, Raman spectroscopy, X-ray diffraction, UV-visible and PL spectroscopy. The as synthesized samples were also tested for their applicability to use as cathode materials for supercapacitor applications. The WSe2 samples prepared by the microwave and hydrothermal methods (with use of tungstic acid as precursor) show noteworthy performance towards supercapacitor application. Our work opens a new avenue to use these simple methods to prepare various morphologies of inorganic nanomaterials and utilize them for various energy and nanoelectronics applications.

Microwave-assisted synthesis of few-layered TaTe2 and its application as supercapacitor - Chakravarty, Disha; Kumar, Praveen; Ugale, Vaishali S.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report a simple and rapid microwave-assisted synthesis of tantalum telluride (TaTe2) nanosheets. The ratio of tantalum pentachloride (TaCl5) and elemental tellurium (Te) powder were adjusted in the presence of NaBH4 in such a way as to obtain the TaTe2 nanosheet. The samples were characterized by various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), UV/Vis spectroscopy, photoluminescence (PL) spectroscopy, and XRD. Our SEM, TEM, and AFM results show the formation of sheet-like morphology, while the XRD data confirms the high crystalline quality and stable phase of the TaTe2 formed. The supercapacitor cells were fabricated by using TaTe2 nanosheets as anode material, platinum metal wire as a counterelectrode, and Ag/AgCl as reference electrode. The calculated coulombic efficiency is more than 95%, while the cycle-to-cycle decrease in capacity is less than 5%. The maximum discharge or charging capacity is below 2.4 Wh/kg, which is an ideal characteristic for achieving supercapacitor behavior.
Keywords: Microwave chemistry; Nanostructures; Supercapacitors; Tantalum; Tellurium

Perspective on atomically thin 2d inorganic layered materials for biosensor - Late, Dattatray J.; Rout, C. S.; Chakravarty, Disha; Ratha, S. (Journal of Nanomedicine Research, 2015)

Pt-nanoparticle functionalized carbon nano-onions for ultra-high energy supercapacitors and enhanced field emission behaviour - Suryawanshi, Sachin R.; Kaware, Vaibhav; Chakravarty, Disha; Walke, Pravin S.; More, Mahendra A.; Joshi, Kavita; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2015)
In the present work, we have investigated the charge storage capacitive response and field emission behaviour of platinum (Pt) nanoparticles decorated on carbon nano onions (CNOs) and compared them with those of pristine carbon nano onions. The specific capacitance observed for Pt-CNOs is 342.5 F g(-1), about six times higher than that of pristine CNOs, at a scan rate of 100 mV s(-1). The decoration with Pt nanoparticles, without any binder or polymer separator on the CNO, leading to enhanced supercapacitance is due to easy accessibility of Na2SO4 electrolyte in the active material. The Density Functional Theory (DFT) calculations of these systems reveal enhancement in the Density of States (DOS) near the Fermi energy (E-F) on account of platinum decoration on the CNOs. Furthermore, the field emission current density of similar to 0.63 mA cm(-2) has been achieved from the Pt-CNOs emitter at an applied electric field of similar to 4.5 V mu m(-1) and from the pristine CNOs sample current density of similar to 0.4 mA cm(-2) has been achieved at an applied electric field of similar to 6.6 V mu m(-1). The observed enhanced field emission behavior has been attributed to the improved electrical conductivity and increased emitting sites of the Pt-CNO emitter. The field emission current stability of the Pt-CNO emitter over a longer duration is found to be good. The observed results imply multifunctional potential of Pt-CNOs, as supercapacitor material in various next generation hybrid energy storage devices, and field emitters for next generation vacuum nano/microelectronic devices.